In Prinkipo (Turkey). From left to right: Zina Trockij, Roman Well (ps. of Ruvin Sobolevicius), Trockij and Adolf Senin (ps. of Abraham Sobolevicius) (1931)
In Prinkipo (Turkey). From left to right: Zina Trockij, Roman Well (ps. of Ruvin Sobolevicius), Trockij and Adolf Senin (ps. of Abraham Sobolevicius).